Mutu Hasil Belajar Aljabar Linear melalui Pembelajaran Daring di Palcomtech Palembang - Leni Maimuna (Universitas Sarjanawiyata Tamansiswa, 2020)
This research is a quantitative study which aims to determine the quality of college student learning outcomes during online learning in Linear Algebra courses. The subjects of this research were 50 college students of Informatics Engineering and Information Systems, STMIK and Polytechnic at Palcomtech Palembang. Data regarding college students' abilities and difficulties were obtained from test methods, documentation and observation during online learning. Online learning that is done through the zoom application and group whatsapp. Data were analyzed to determine the quality of Linear Algebra learning outcomes through online learning. Based on the data obtained from college student scores, namely 8 independent assignments, 2 quizzes, Mid-Semester Exams and Final Semester Exams during online learning in Linear Algebra courses, the average college student grade was 76.67. The value category is in a high range, which is good.